2006
DOI: 10.1016/j.brainresbull.2006.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic methylphenidate dose–response assessment on three adolescent male rat strains

Abstract: Methylphenidate (MPD), commonly known as Ritalin, is the most frequently prescribed drug to treat children and adults with attention deficit hyperactivity disorder (ADHD). Adolescence is a period of development involving numerous neuroplasticities throughout the central nervous system (CNS). Exposure to a psychostimulant such as MPD during this crucial period of neurodevelopment may cause transient or permanent changes in the CNS. Genetic variability may also influence these differences. Thus, the objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 66 publications
(82 reference statements)
4
75
1
Order By: Relevance
“…Additionally, there is no sex difference in hyperactivity in the SHR strain (Berger and Sagvolden 1998). Moreover, SHR show hyperactivity when compared to WKY rats but they are not more active than other outbred rat strains such as Wistar and SpragueDawley rats (Ferguson and Cada 2003;Yang et al 2006;Hård et al 1985;Goto et al 1993;Ernsberger et al 1983;Paré 1989;Sagvolden et al 1993).…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, there is no sex difference in hyperactivity in the SHR strain (Berger and Sagvolden 1998). Moreover, SHR show hyperactivity when compared to WKY rats but they are not more active than other outbred rat strains such as Wistar and SpragueDawley rats (Ferguson and Cada 2003;Yang et al 2006;Hård et al 1985;Goto et al 1993;Ernsberger et al 1983;Paré 1989;Sagvolden et al 1993).…”
Section: Introductionmentioning
confidence: 91%
“…It has also been reported that there are strain differences in the effects of MPH administered to juvenile rats (Yang et al, 2006). Male spontaneously hyperactive/hypertensive rats, Wistar-Kyoto rats, and Sprague-Dawley rats, 34-41 days old, were administered MPH via intraperitoneal injections on a single day or for 11 days at doses of 0.6, 2.5, or 10.0 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [15]- [20] [25]- [27] using identical protocol reported minor, insignificant fluctuations in the behavioral and electrophysiological study of rats injected with saline vs. rats that received no injection. The above studies have shown that time (42 days) and repetitive saline injections (42 days) exhibit similar activity with minor and insignificant fluctuations [15] [16] [19]. This permits the use of saline injection at ED 1 as a control for the drug effect (injections (0.8 ml) and handling of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…), are calculated as freebase. Dosages were selected from prior MPD dose response studies [6] [14]- [19] [21]. These studies assessed the dose responses of eight different concentrations of MPD, in which three were selected.…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation